ASSESSMENT IN THE NEW PARADIGM LEARNING - David Firna Setiawan; Mahmud Yunus; Buyung Kusumawardhana; Endang Wuryandini (Proceeding International Conference on Digital Education and Social Science, 2022)
At the primary and secondary education levels, the assessment (assessment) process in the cognitive domain is generally carried out in the form of tests. In the new paradigm of learning, the method does not seem to be used enough to collect information to find out the learning needs and developmental achievements or learning outcomes of students. Through the decision of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia (Kemenristekdikti) Number 162/M/2021 concerning the Motivating School Program, a new term called learning with a new paradigm was introduced. Through this concept, assessment activities carried out by teachers need to be adjusted. This article aims to propose ideas on assessment procedures that teachers can follow. The literature review method is used to analyze the relevance of the learning concept to the new paradigm and differentiated learning, as well as to describe the assessment procedure in differentiated learning.